Optimization of a methodology for simultaneous determination of four antidepressants present in fresh water by high efficiency liquid chromatography - Evagelista, Patrícia Alexandre; Vilca, Franz Zirena; Pimpinato, Rodrigo Floriano; Tornisielo, Valdemar Luiz (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2022)
The occurrence of emerging contaminants is a growing concern in the environmental scenario due to their potential risks to ecosystems. The technologies employed in the treatment of sewage in Brazil are not efficient in removing micropollutants, especially persistent ones. Antidepressants (a class of drugs belonging to emerging contaminants) can reach the environment through the disposal of domestic and industrial effluents. These substances were detected in studies with surface waters, being able to cause changes and accumulate in aquatic organisms. The occurrence and impacts of this class of pollutant are still poorly studied in the country. Thus, there is a need to carry out environmental monitoring. To meet such a goal, scientific advances must be developed, especially those related to the development of analytical skills, equipment, and methods with the necessary sensitivity to research in the different sources of contamination. Accordingly, with the development of analytical techniques, it is possible to determine antidepressant drugs in environmental and / or biological matrices in increasingly small concentrations. Consequently, optimization of current techniques and proposing new ones are crucial before any other actions. The aim of this study was to validate a rapid methodology for determining the presence of four antidepressants - fluoxetine, citalopram, venlafaxine, and sertraline - in fresh water through high performance liquid chromatography. The method involved solid-phase extraction (SPE) with C18 cartridge and quantification by high performance liquid chromatography coupled to a diode array detector with C8 column. No chromatographic interference was observed in the retention time of the antidepressants in this study at the selected wavelength of 235 nm. The study matrix did not interfere in the analyses. Linearity was adequate for the range from 0.5 to 10 µg mL-1, with limits of detection and quantification of 0.03 to 0.09 µg mL-1 and 0.10 to 0.27 µg mL-1 respectively. Accuracy was assessed by testing sample fortification at three concentration levels and estimated by relative standard deviation (RSD). RSD values below 15% were obtained. The recovery interval ranged from 49 to 102%. The analytical method was validated and considered satisfactory for the simultaneous determination of antidepressants in freshwater samples using a C8 column.